Memory Profiles after Unilateral Paramedian Thalamic Stroke Infarction: A Comparative Study - Antonio Carota; Herbert Neufeld; Pasquale Calabrese (Case Reports in Medicine)
We performed extensive neuropsychological assessment of two male patients (matched for age and educational level) with similar (localization and size) unilateral paramedian ischemic thalamic lesions (AB on the left and SD on the right). Both patients showed severe memory impairments as well as other cognitive deficits. In comparison to SD, AB showed severe impairment of executive functions and a more severe deficit of episodic/anterograde memory, especially in the verbal modality. The findings of this single case study suggest the possibility that the profile and severity of the executive dysfunction are determinant for the memory deficits and depend on from the side of the lesion. In addition to a material-side-specific (verbal versus visual) deficit hypothesis, the differential diencephalo-prefrontal contributions in mnestic-processing, in case of paramedian thalamic stroke, might also be explained in terms of their stage-specificity (encoding versus retrieval).